Development of Commercial Sterility Detection Method Based on Chromogenic Media Agar in UHT Coconut Cream Liquid Products - Tangkau, Ester Ruth Youla; Rori, Chindy Achika; Kamto, Yoel William Prasetyo; Mangangantung, Brayen; Tangapo, Agustina Monalisa (Universitas Sam Ratulangi, 2025)
Commercial sterility analysis is a crucial step in quality control of Ultra High Temperature (UHT) products such as coconut cream liquid products produced by PT Sasa Inti Minahasa Selatan, to ensure the safety and stability of shelf life. Stability incubation testing takes a long time, which is 7-14 days. Development of commercial sterility methods using Chromogenic Agar selective media is needed to cut the incubation time that is too long. Agar Chromogenic Media is tested for its ability to detect common contaminants in UHT coconut cream products, in particular thermophilic and mesophilic microorganisms that cause spoilage, with a short incubation time. UHT coconut cream samples are prepared by artificial and natural inoculation. Validation was carried out by comparing the results on standard media based on sensitivity, specificity and Time-to-result (TTR) parameters. The results showed a real difference between NA/TGEA media and chromogenic media so that the reading of bacterial colonies growing on chromogenic media was clearer and easier to read due to the change in color and short incubation time where the bacteria causing decay had grown on day 5 with a reading of results that took only 24 hours. Based on the validation that has been carried out, chromogenic selective media can accelerate product release time and improve quality control efficiency in the UHT coconut cream industry.